2003
DOI: 10.1007/s00421-002-0783-1
|View full text |Cite
|
Sign up to set email alerts
|

Methodological aspects of maximal lactate steady state—implications for performance testing

Abstract: The maximal lactate steady state (MLSS) is the highest blood lactate concentration (BLC) that can be identified as maintaining a steady-state during a prolonged submaximal constant workload. Comparative interpretation of published data about MLSS is complicated by the fact that different methods of testing have been utilized. Thus, three methods, corresponding to the time course of changes in BLC incurred during either 30 min (MLSS I) or 20 min (MLSS II and III) of constant submaximal workload exercise, were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
182
1
44

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(235 citation statements)
references
References 9 publications
8
182
1
44
Order By: Relevance
“…An ergometric rowing study demonstrated for V 4 what was found in this study for the thresholds of fixed velocity, meaning velocity values above those predicted by MLSS, and high correlation (r = 0.80) between them using 3 min stages (Beneke, 2003). For athletes in cycloergometry, a low correlation was reported (r = 0.57) between fixed velocities at 4 mmol.L -1 and those predicted by MLSS (Aunola and Rusko, 1992).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…An ergometric rowing study demonstrated for V 4 what was found in this study for the thresholds of fixed velocity, meaning velocity values above those predicted by MLSS, and high correlation (r = 0.80) between them using 3 min stages (Beneke, 2003). For athletes in cycloergometry, a low correlation was reported (r = 0.57) between fixed velocities at 4 mmol.L -1 and those predicted by MLSS (Aunola and Rusko, 1992).…”
Section: Discussionsupporting
confidence: 68%
“…Studies are necessary to determine if these factors, inherent to the field test, influence incremental and constant load exercises differently and, consequently, their comparison. Additionally, this study used the method initially proposed for assessment of MLSS (Heck et al, 1985), which was later modified by investigators and which is currently more used and accepted by the scientific community in human sports (Beneke, 2003), using a protocol with 30 min of duration. This difference would probably alter the results of the comparison between the methods.…”
Section: Discussionmentioning
confidence: 99%
“…Dentre os diversos protocolos e critérios, a máxima fase estável de lactato sanguíneo (MLSS) tem sido considerada como o padrão-ouro para a avaliação aeróbia (1)(2)(3) . A MLSS pode ser definida com a maior intensidade de exercício de carga constante onde ainda pode ser observada estabilidade na concentração sanguínea de lactato.…”
Section: Introductionunclassified
“…During constant load exercise, the calculation of substrate utilization by means of indirect calorimetry is correct as long as there are lactate steady-state conditions [ 12 ] . If the lactate steady-state is defi ned as no more than 1 mmol/l increase in bLa between the 10 th and 30 th minute of exercise [ 5 ] , 3 subjects were not in a lactate steady-state in the constant load test at Fat max and fi ve were not in a lactate steady state in the HIGH test. In this case, non-metabolic CO 2 comes up through the buff ering of hydrogen-ions, aff ects RER and, therewith, the calculated fat oxidation rate.…”
mentioning
confidence: 99%